Randomized Phase II Trial of Erlotinib Beyond Progression in Advanced Erlotinib‐Responsive Non‐Small Cell Lung Cancer. (25th August 2015) - Halmos, Balazs; Pennell, Nathan A.; Fu, Pingfu; Saad, Shumaila; Gadgeel, Shirish; Otterson, Gregory A.; Mekhail, Tarek; Snell, Michael; Kuebler, J. Philip; Sharma, Neelesh; Dowlati, Afshin
Abstract : Background: Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) therapy is clearly beneficial in patients with advanced EGFR‐mutated non‐small cell lung cancer (NSCLC). However, acquired resistance develops uniformly and the benefit of continuation of EGFR TKI therapy beyond progression remains unclear. Materials and Methods: This was a randomized phase II study of chemotherapy (arm A: pemetrexed or docetaxel) versus chemotherapy plus erlotinib (ERL) (arm B) in patients with progressive NSCLC following clinical benefit from erlotinib. In arm B, chemotherapy was given with erlotinib at an oral daily dose of 150 mg on days 2–19 of each cycle to minimize negative pharmacodynamic interactions. The primary endpoint was that continuation of erlotinib in this patient population could extend progression‐free survival (PFS) by 50%. Results: A total of 46 patients were randomized (arm A: 24; arm B: 22). Patient characteristics were well balanced except there were more female patients in arm A ( p = .075). The median PFS of patients in arm A was 5.5 months and for those in arm B, 4.4 months ( p = .699). The response rates were 13% and 16% in arms A and B, respectively ( p = .79). EGFR status data were available for 39 of the 46 patients and no significant difference in PFS was seen for continuing ERL beyond progression in mutation‐positive patients. Substantially more toxicity was seen in arm B than arm A. Conclusion: There was added toxicity but no benefit with the continuation of ERL beyond progression along with chemotherapy as compared with chemotherapy alone. Implications for Practice: The benefits of continuing erlotinib upon progression alongside conventional chemotherapy are unclear. This randomized phase II study, initiated prior to the establishment of routine epidermal growth factor receptor (EGFR) mutation testing, addressed this clinically relevant issue through randomizing patients with prior clinical benefit from erlotinib (thereby enriching for EGFR‐mutated tumors) upon progression in the second‐ or third‐line setting to conventional chemotherapy (single‐agent pemetrexed or docetaxel) with or without continued erlotinib. The results showed no benefit to continuing erlotinib beyond progression, while significantly more side effects were noted in the combination arm. Along with other recently presented study findings, these results argue against the routine practice of continuing erlotinib in this setting. Abstract : This was a randomized phase II study of chemotherapy (arm A: pemetrexed or docetaxel) versus chemotherapy plus erlotinib (ERL) (arm B) in 46 patients with progressive non‐small cell lung cancer following clinical benefit from ERL. The primary endpoint was that continuation of erlotinib in this patient population could extend progression‐free survival (PFS) by 50%. No significant difference in PFS was seen for continuing ERL beyond progression in mutation‐positive patients, and patients in arm A experienced more toxicity. Abstract : 摘要 背景 . 对于表皮生长因子受体 (EGFR) 突变的晚期非小细胞肺癌 (NSCLC) 患者, EGFR 酪氨酸激酶抑制剂 (TKI) 治疗有明确的获益。但患者均会发生获得性耐药, 而进展后继续 EGFR TKI 治疗的获益尚不明确。 方法 . 本研究为随机 II 期临床研究, 在厄洛替尼治疗有临床获益的 NSCLC 患者发生进展后对化疗(A 组: 培美曲塞或多西他赛) 与化疗联合厄洛替尼 (ERL) (B 组) 进行比较。B 组在化疗的同时, 还给予厄洛替尼 150 mg 每日一次口服, 在每个治疗周期的 D2 ∼ D29 给药, 以将不利药效动力学相互作用降至最小。主要终点为该患者人群继续厄洛替尼治疗可使无进展生存 (PFS) 增加 50%。 结果 . 共 46 例患者进入随机分组(A 组: 24 例, B 组: 22 例)。除A组女性较多以外( P = 0.075), 两组患者特征分布均衡。A 组的中位 PFS 为 5.5 个月, B 组为 4.4 个月 ( P = 0.699)。A 组缓解率为 13%, B 组为 16% ( P = 0.79)。39/46 例患者有 EGFR 状态数据, 突变阳性患者进展后继续 ERL 治疗的 PFS 差异无统计学意义。B 组的毒性事件明显多于A 组。 结论 . 与单用化疗相比, 进展后继续ERL联合化疗毒性增加而未见获益。The Oncologist 2015;20:1298–1303 对临床实践的提示 :进展后给予传统化疗的同时继续厄洛替尼治疗的获益尚不明确。本项随机 II 期研究开始于常规表皮生长因子 (EGFR) 突变检测确认阳性之前, 通过将曾从厄洛替尼治疗中得到临床获益的患者 (因此聚集了 EGFR 突变肿瘤患者) 在发生进展后进行随机分配, 于之后的二线或三线治疗中在传统化疗 (培美曲塞或多西他赛单药) 基础上联合或不联合继续厄洛替尼治疗, 从而解决了前述的问题。结果显示进展后继续厄洛替尼治疗没有获益, 而联合组中还观察到明显较多的不良反应。考虑到近期发表的其他研究结果, 这些结果反对在该人群中继续使用厄洛替尼作为常规方案。